2004
DOI: 10.1083/jcb.200409077
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastin is a cell adhesion molecule required for maintaining the differentiation state of ameloblasts

Abstract: Tooth morphogenesis results from reciprocal interactions between oral epithelium and ectomesenchyme culminating in the formation of mineralized tissues, enamel, and dentin. During this process, epithelial cells differentiate into enamel-secreting ameloblasts. Ameloblastin, an enamel matrix protein, is expressed by differentiating ameloblasts. Here, we report the creation of ameloblastin-null mice, which developed severe enamel hypoplasia. In mutant tooth, the dental epithelium differentiated into enamel-secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
410
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(429 citation statements)
references
References 41 publications
17
410
0
2
Order By: Relevance
“…We found that p75 was expressed in an undifferentiated dental epithelial cell line but was not detectable in the tooth germ. It was reported that in incisors, p75 is expressed in the inner dental epithelium but is completely absent in differentiated ameloblasts (6). Further, the possibility of epithelial-mesenchymal communication within the intact tooth germ, whereas there is complete absence of those effects in the individual cells cultures, may be at the root of the differences of p75 expression between tooth germ and dental epithelial cell cultures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We found that p75 was expressed in an undifferentiated dental epithelial cell line but was not detectable in the tooth germ. It was reported that in incisors, p75 is expressed in the inner dental epithelium but is completely absent in differentiated ameloblasts (6). Further, the possibility of epithelial-mesenchymal communication within the intact tooth germ, whereas there is complete absence of those effects in the individual cells cultures, may be at the root of the differences of p75 expression between tooth germ and dental epithelial cell cultures.…”
Section: Discussionmentioning
confidence: 92%
“…Ambn, also known as amelin or sheathlin, is a tooth-specific glycoprotein that represents the most abundant non-Amel enamel matrix protein. We previously created Ambn-null mice, which develop severe enamel hypoplasia in which ameloblasts detached from the matrix, lost cell polarity, resumed proliferation, and formed multiple cell layers (6). These results suggest that Ambn is essential for ameloblast differentiation and enamel formation.…”
mentioning
confidence: 99%
“…Amelogenin protein lacks canonical integrin binding motifs; however, another rodent enamel protein, ameloblastin, does contain an RGD motif and has been shown to be involved with attachment of the ameloblasts to the matrix (29,30). Therefore, we used anti-integrin ␣6 antibodies (31) to examine the distribution of integrin molecules localized to the Tomes' processes.…”
Section: Resultsmentioning
confidence: 99%
“…The amelogenesis process is divided into the presecretory stage, secretory stage, and maturation stage, with marker genes expressed at each phase. Over the past decade, mouse models engineered for the loss-of-function analyses of AMEL (29), AMBN (30,31), ENAM (32), MMP20 (33), and KLK4 (34) have been reported. Among these engineered models, the enamel defects of Ambn KO and Enam KO mice (35) were very similar to those of the Fam20C KO mice.…”
Section: Fam20c Is Essential To Tooth Formationmentioning
confidence: 99%